Pengelolaan Sampah Rumah Tangga Berbasis Masyarakat Di Wilayah Kerja Puskesmas Selemadeg II Kecamatan Selemadeg Timur Kabupaten Tabanan - I Nyoman Purna; I Nyoman Sujaya; M. Choirul Hadi; I Wayan Jana; Ni Ketut Rusminingsih (Jurnal Pengabmas Masyarakat Sehat, 2019)
The amount of waste will continue to increase along with increasing population growth. The increasing number of people will increase the amount of waste will also increase. Increasing volume of waste from year to year is a strong reason that waste problems are the main problem that must be solved in the short, medium and long term. Waste management according to Law 18 of 2008 is a systematic, comprehensive and sustainable activity that includes reduction and handling of waste. Waste management is carried out by the community including: Waste Management, Domestic Systems, Waste Collection-Systems, Independent and Productive Systems, Waste Savings Systems in Waste Banks. The purpose of this community service is to understand how to carry out community-based independent waste management. To be able to sort waste in their respective households, they want to collect waste that has been sorted into a trash while available. The results of the community service and commitment to always maintain the environment by segregating organic and inorganic waste and collecting inorganic waste shelters before being followed up and sold to collectors.Keywords: Community Based Waste Management.